Design, synthesis, and biological evaluation of novel carbazole derivatives as potent DNMT1 inhibitors with reasonable PK properties - Ennian Li; Kai Wang; Bei Zhang; Siqi Guo; Senhao Xiao; Qi Pan; Xiaowan Wang; Weiying Chen; Yunshan Wu; Hesong Xu; Xiangqian Kong; Cheng Luo; et al. (Journal of Enzyme Inhibition and Medicinal Chemistry)
The DNA methyltransferases (DNMTs) were found in mammals to maintain DNA methylation. Among them, DNMT1 was the first identified, and it is an attractive target for tumour chemotherapy. DC_05 and DC_517 have been reported in our previous work, which is non-nucleoside DNMT1 inhibitor with low micromolar IC50 values and significant selectivity towards other S-adenosyl-L-methionine (SAM)-dependent protein methyltransferases. In this study, through a process of similarity-based analog searching, a series of DNMT1 inhibitors were designed, synthesized, and evaluated as anticancer agents. SAR studies were conducted based on enzymatic assays. And most of the compounds showed strong inhibitory activity on human DNMT1, especially WK-23 displayed a good inhibitory effect on human DNMT1 with an IC50 value of 5.0 µM. Importantly, the pharmacokinetic (PK) profile of WK-23 was obtained with quite satisfying oral bioavailability and elimination half-life. Taken together, WK-23 is worth developing as DNMT1-selective therapy for the treatment of malignant tumour.